LAR-RPTP Clustering Is Modulated by Competitive Binding between Synaptic Adhesion Partners and Heparan Sulfate - Won, Seoung Youn; Kim, Cha Yeon; Kim, Doyoun; Ko, Jaewon; Um, Ji Won; Lee, Sung Bae; Buck, Matthias; Kim, Eunjoon; Heo, Won Do; Lee, Jie-Oh; Kim, Ho Min (Frontiers in Molecular Neuroscience, 2017)
The leukocyte common antigen-related receptor protein tyrosine phosphatases (LAR-RPTPs) are cellular receptors of heparan sulfate (HS) and chondroitin sulfate (CS) proteoglycans that direct axonal growth and neuronal regeneration. LAR-RPTPs are also synaptic adhesion molecules that form trans-synaptic adhesion complexes by binding to various postsynaptic adhesion ligands, such as Slitrks, IL1RAPL1, IL-1RAcP and TrkC, to regulate synaptogenesis. Here, we determined the crystal structure of the human LAR-RPTP/IL1RAPL1 complex and found that lateral interactions between neighboring LAR-RPTP/IL1RAPL1 complexes in crystal lattices are critical for the higher-order assembly and synaptogenic activity of these complexes. Moreover, we found that LAR-RPTP binding to the postsynaptic adhesion ligands, Slitrk3, IL1RAPL1 and IL-1RAcP, but not TrkC, induces reciprocal higher-order clustering of trans-synaptic adhesion complexes. Although LAR-RPTP clustering was induced by either HS or postsynaptic adhesion ligands, the dominant binding of HS to the LAR-RPTP was capable of dismantling pre-established LAR-RPTP-mediated trans-synaptic adhesion complexes. These findings collectively suggest that LAR-RPTP clustering for synaptogenesis is modulated by a complex synapse-organizing protein network.